Mindfulness and the ethics of intercultural knowledge-work. (2nd January 2017) - Huang, Zhuo Min; Fay, Richard; White, Ross
ABSTRACT: Mindfulness, or 念 (niàn) in Chinese, is a concept and set of related practices which have both ancient Eastern roots and current popularity (especially in the West). It provides a fascinating example of intercultural knowledge-work involving a complex set of conceptual migrations through time and space, across languages and cultures, and within domains and disciplines. We first review the vitality of the concept as used in Western disciplines (chiefly intercultural communication and psychotherapy), noting how the Eastern origins are mentioned but not fully discussed. We then review the ancient origins in Eastern religious and philosophical thinking concluding with an account of the development of the term in the East until recent times. As we discuss next, when these differing arenas of use and development interact, understandings become contested and issues of privilege vis-á-vis knowledge sources can be seen. These complexities raise questions about authenticity versus translation with regard to the differing uses made of the concept in the different arenas. Learning from the reviews of the differing understandings of this concept and the sometimes fraught interactions between them, we propose that scholars and practitioners working in our highly interconnected era, adopt an intercultural ethic to regulate and guide such knowledge-work.